Effect of seed coating with polymer and chemicals on longevity of maize (Zea mays L.) - Dhiman, Shikha (Journal of Cereal Research, 2023)
High-quality seed’s viability and longevity during storage are crucial for sustainable agricultural production. The present storage experiment was conducted under ambient conditions using maize composite variety “Bajaura Makka”. Seeds treated with polymer and chemicals were subjected to assess the seed quality in order to know the effect of seed coating on seed longevity during storage and to identify the effective seed coating treatment for enhancing seed longevity. A total of ten treatment combinations (nine coated + one uncoated/control) packed in HDPE (high density polyethylene) interwoven bags were stored in Completely Randomized Design (CRD) in three replications for twelve months (March, 2021). These ten treatment combinations were carried over for another twelve months (13th to 24th months i.e., from March 2022 to March 2023) and observations were recorded on seed quality parameters. All the recorded seed quality parameters showed reduction with the passage of the storage period despite of various seed coating treatments. The treatments, T6 - polymer + vitavax power (containing thiram 37.5% and carboxin 37.5%) @ 2 g/kg of seed and T5 - vitavax power (containing thiram 37.5% and carboxin 37.5%) @ 2 g/kg seed recorded significantly higher seed quality parameters viz., germination percentage - first count (93.67%, 93.00%), germination percentage - final count (94.00%, 93.00%), rate of germination (43.30, 43.20), seedling length (33.73 cm, 33.63 cm), dry matter of seedling (60.01 mg, 59.83 mg ), seedling vigour index - I (3170.93, 3128.00), seedling vigour index - II (5640.94, 5564.72), field emergence percentage (80.67%, 79.67%) and final plant stand percentage (80.67%, 79.67%), respectively over T1 - control after 24 months of  storage period. The treatment T6 showed an increase of 8.91%, 9.30%, 8.25%, 7.45%, 7.16%, 17.45%, 17.13%, 11.52%, 11.52%, while treatment T5 showed an increase of 8.14%, 8.14%, 8.00%, 7.14%, 6.85%, 15.86%, 15.55%, 10.14%, 10.14% over T1 - control for seed quality parameters viz., germination percentage first count, germination percentage final count, rate of germination, seedling length, dry matter of seedling, seedling vigour index - I, seedling vigour index -  II, field emergence percentage and final plant stand percentage, respectively after 24 months of storage period.